QUESTIONS ON ETHICS AND BEYOND IN SCIENCE EDUCATION—EXPLORING THROUGH THE LENS OF GENE EDITING - Shimray, Chong (SCHOOL SCIENCE, 2025)
Science has brought about unimaginable technological advancements, which have benefited humanity in numerous ways, such as in the field of communication, transport, healthcare, food production, etc. Of these, genetic engineering in general and gene editing in particular are such areas that have opened endless avenues to address health-related issues. However, such remarkable advancements have also brought in ethics-related questions, which are found to be addressed inadequately in the science curriculum. The bigger and philosophical questions such as 'to what end?' or 'what is our ultimate goal?' are overlooked in science classrooms. When such fundamental questions are critically discussed in science classrooms, it is likely to guide or direct how we do science and thereby our research and innovations. This article explores such questions on ethics and even beyond ethics in science education by using gene editing as a context. It argues the need to engage students on those questions so that they are not only aware about those critical questions but are also able to take informed, ethical and responsible decisions as researchers, scientists, engineers, policymakers, etc. Some suggestions on how such concerns can be integrated and addressed in science education have also been provided. The National Education Policy 2020 has also recommended such ethical considerations